2012
DOI: 10.1590/s1984-29612012000300033
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-Borrelia burgdorferi antibodies in buffaloes (Bubalus bubalis) in the state of Pará, Brazil

Abstract: Detection of anti-Borrelia burgdorferi antibodies in buffaloes (Bubalus bubalis) in the state of Pará, Brazil AbstractThis study aimed to investigate the frequency of homologous antibodies of IgG class against Borrelia burgdorferi in buffaloes in the state of Pará, Brazil. Blood serum samples from 491 buffaloes were analyzed by means of the indirect ELISA test, using crude antigen produced from a cultivar of the North American strain G39/40 of B. burgdorferi. There were 412 positive samples (83.91%), and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…has been studied in different animal species at Rio de Janeiro (RJ), São Paulo (SP) and Pará (PA) states and these studies have shown prevalences, ranging from 9.7% to 83.91% using different sorological methodologies (ALVES et al, 2004;CORDEIRO et al, 2012;CORREA et al, 2012;JOPPERT et al, 2001;SOARES et al, 1999). It is important to emphasize that among dogs, the frequency of these antibodies has doubled in the last 14 years in the Rio de Janeiro state (SOARES et al, 2000;ALVES et al, 2004;CORDEIRO et al, 2012, SOARES et al, 1999.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…has been studied in different animal species at Rio de Janeiro (RJ), São Paulo (SP) and Pará (PA) states and these studies have shown prevalences, ranging from 9.7% to 83.91% using different sorological methodologies (ALVES et al, 2004;CORDEIRO et al, 2012;CORREA et al, 2012;JOPPERT et al, 2001;SOARES et al, 1999). It is important to emphasize that among dogs, the frequency of these antibodies has doubled in the last 14 years in the Rio de Janeiro state (SOARES et al, 2000;ALVES et al, 2004;CORDEIRO et al, 2012, SOARES et al, 1999.…”
Section: Resultsmentioning
confidence: 99%
“…antibodies in cattle, buffalos, equines, dogs and humans (CORREA et al, 2012;DANTAS-TORRES, 2008;JOPPERT et al, 2001). …”
Section: Introductionmentioning
confidence: 99%